Historical Analysis of Medical Development Issues in International Relations of Uzbekistan (In the case of Navoi region) (Eurasian Medical Research Periodical, 2023)
In this article, after the independence of Uzbekistan, in the first years, international relations were established in order to improve the health infrastructure in the country, and the work was carried out to assimilate the experience of developed countries - Germany, France, Great Britain, Turkey, India, Israel, Russia, the USA, providing medical services to the population, providing medical staff with new modern knowledge, building and equipping hospitals at the level of modern requirements in cooperation with foreign countries, reconstructing the existing ones, providing them with sufficient medicine, medical equipment, and in particular Navoi Opinions were expressed about the work carried out in the region.